Shock adiabat analysis for the mixture of liquid and gas of two components - Hai, Duong Ngoc; Tuan, Nguyen Van (Vietnam Journal of Mechanics, 2000)
The liquid and gas mixture is met in many natural and industrial processes. In the paper, the investigation results of shock waves, propagated in the liquid and two-component gas (one component is neutral, the other is condensed) mixture, are presented. The influence of the relative gas ratios, initial gas volume, wave intensity etc. on the main wave characteristics, is analyzed and illustrated as examples for two mixtures. The first is a mixture of water and gas (air and water vapor). The second is a mixture of crude oil and gas (one component is soluble, the other is insoluble).